The effect of reaction temperature on the formation of 2H-SiC and 3C-SiC nanowhiskers - Dzulkifli, H. (Growing Science, 2020)
Synthesis of 2H and 3C-polytype silicon carbide nanowhiskers mixture of silicon dioxide and carbon was performed by carbothermal reduction process. The reaction temperature for synthesis of 2H-SiC was varied from 1350 C to 1650 C and for the 3C-SiC this range was varied from 1450 C to 1650 C. Scanning Electron Microscopy (SEM) analyses showed that nanowhiskers structures of both 2H-SiC and 3C-SiC polytypes has a size up to 100 nm in diameters and several microns in length. However, the orientation and pattern of grains were different in both structures. While for 3C-SiC polytype, the shape has been classified as SiC majorly grew along 101 plane by X-ray Diffraction pattern and finalized by Raman shift peaks at 799 and 959 cm-1, the shape of 2H-polytipe silicon carbide was categorized as SiC majorly grown along 111 plane confirmed by Raman shift peak at 799 and 963 cm-1. The mechanism of vapor-gas interaction was also suggested and discussed for both SiC nanowhiskers polytypes. Â© 2020 Growing Science Ltd. All rights reserved. Â© 2020 by the authors; licensee Growing Science, Canada.